IDEOLOGEMES IN KOCHO RACIN’S SHORT STORIES (Philological Studies, 2025)
The paper tackles the problem of the meaning and interpretation of Racin’s short stories, considering the ideologemes presented in these texts. The points of departure in this analysis are the theoretical approaches to a literary text understood as an ideological act and viewedfrom a hermeneutic perspective, and the one on the theory of reception, which enables the overview of the semiotic relations between the type (seen as a genre of certain text) and the implication, involving the denotation and connotation. These reflections are followed by elaborations on the ideologeme, as presented in the works of Hegel, Pavel Medvedev, Mikhail Bakhtin, Julia Kristeva, and Fredric Jameson. They carefully consider this notion and the correlation between the circumstances in which one text appears and the broader culture, the way they communicate and influence each other. Through meticulous analysis, we differentiate five dominant ideologemes in Racin’s short stories: the awareness, rock breaker, tobacco, city, and jail as means by which the semiosis in the text is being induced. Considering Racin’s reflections on how art should represent reality, it can be inferred that ideologemes in Racin’s short stories serve as discrete signals for social dynamics, imbued with semantic power and undeniable clarity. They become an indicator of his skillful artistic manner, which is not undermined by the success of his poetry and his widely recognized poetic gift.
Keywords: significance of the literary work, idea, ideologeme, short story, Racin